P153 Tocilizumab in systemic sclerosis: real world experience from a single centre cohort supports potential benefit on lung function for anti-topoisomerase (Scl-70) positive subgroup. (20th April 2020) - Clark, Kristina E. N; Suleman, Yasir; Nihtyanova, Svetlana I; Ong, Voon H; Denton, Christopher P
Abstract: Background: The FaSScinate and FocuSSced trials of tocilizumab versus placebo in early diffuse systemic sclerosis (SSc) highlighted the potential impact of tocilizumab on lung function with preservation of lung function in those treated with tocilizumab versus placebo, despite only a trend of benefit for skin fibrosis. Our centre have been using tocilizumab to treat SSc patients and overlap inflammatory arthritis, in line with NICE guidance treatment for inflammatory arthritis. We report here our experience of tocilizumab in SSc and the impact on lung function. Methods: A retrospective medical chart review of patients attending our centre with SSc and having ever been on tocilizumab were identified, mostly with overlap inflammatory arthritis. Patients included in the FaSScinate trial were excluded, however patients receiving compassionate use of tocilizumab following the phase 3 FocuSSced trial were included. Mann-Whitney-U test was used for statistical analysis. Results: In total 32 patients were identified. 68.8% (n = 22) of patients had a diagnosis of dcSSc. 75% (n = 24) patients were female. The most common autoantibodies were ATA (anti-topoisomerase antibody) (34.3%) and ARA (anti-RNA polymerase-III antibody) (18.8%). 46.9% (n = 17) patients had known interstitial lung disease. 6 patients received tocilizumab on a compassionate basis following completion of the open label phase of the focuSSced clinical trial, the remainder had overlap inflammatory arthritis. Mean age of disease onset was 38.6 years, and the median disease duration to tocilizumab initiation was 7.9 years. 11 patients discontinued tocilizumab: 6 due to cessation of the compassionate use access, 2 due to side effects, 3 due to lack of benefit. 75% (n = 24) patients had serial lung function data to compare FVC and DLCO before and after initiation of treatment. Baseline FVC prior to tocilizumab was 3.09L (sd = 0.98). To standardise results, the yearly change rate in FVC and DLCO was calculated. Median change in % predicted FVC was -1.5% (IQR=0.107) and median change in % predicted DLCO was -0.5% (IQR=0.061). Subgroup analysis revealed a significant difference between autoantibody groups and change in FVC while on tocilizumab. It was notable that there was an increase in median change in FVC in patients with ATA antibody (3.27%, IQR=0.1355) whereas there was a decrease in median change in FVC in all other autoantibody groups (-4.7%, IQR=0.111, p = 0.0019). There was a near significant difference in change in DLCO between these antibodies at 12 months (p = 0.056) in favour of improvement in ATA subgroup. Conclusion: We report our experience of the impact of tocilizumab on lung function in SSc. Consistent with trial results, there is a signal of potential benefit for lung function among those with ATA autoantibody irrespective of disease subset. As this autoantibody confers high risk of extensive lung fibrosis in SSc it may help in future case selection. Disclosures: K.E.N. Clark None. Y. Suleman None. S.I. Nihtyanova None. V.H. Ong None. C.P. Denton Grants/research support; Actelion, GlaxoSmithKline, Bayer, Sanofi, lnventiva, Boehringer Ingelheim, Roche, Bristol Myers Squibb, CSL Behring, UCB, Leadiant Biosciences.